COVID-19 and the risk of CNS demyelinating diseases: A systematic review - Lotan, Itay; Nishiyama, Shuhei; Manzano, Giovanna S.; Lydston, Melissa; Levy, Michael (Frontiers in Neurology, 2022)
Background Viral infections are a proposed possible cause of inflammatory central nervous system (CNS) demyelinating diseases, including multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD), and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). During the past 2 years, CNS demyelinating events associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection have been reported, but causality is unclear. Objective To investigate the relationship between CNS demyelinating disease development and exacerbation with antecedent and/or concurrent SARS-CoV-2 infection. Methods A systematic literature review of all publications describing either a new diagnosis or relapse of CNS demyelinating diseases (MS, NMOSD, MOGAD) in association with SARS-CoV-2 infection was performed utilizing PRISMA guidelines. Descriptive statistics were used for data analysis, using a case analysis approach. Results Sixty-seven articles met the inclusion criteria for the study. Most of the reported cases of NMOSD (n = 13, 72.2% of reported cases) and MOGAD (n = 27, 96.5% of reported cases) were of new disease onset, presenting with typical clinical and radiographic features of these conditions, respectively. In contrast, reported MS cases varied amongst newly diagnosed cases (n = 10, 10.5% of reported cases), relapses (n = 63, 66.4%) and pseudo-relapses (n = 22, 23.2%). The median duration between COVID-19 infection and demyelinating event onset was 11.5 days (range 0–90 days) in NMOSD, 6 days (range−7 to +45 days) in MOGAD, and 13.5 days (range−21 to +180 days) in MS. Most cases received high-dose corticosteroids with a good clinical outcome. Conclusion Based upon available literature, the rate of CNS demyelinating events occurring in the setting of preceding or concurrent SARS-CoV-2 infection is relatively low considering the prevalence of SARS-CoV-2 infection. The clinical outcomes of new onset or relapsing MS, NMOSD, or MOGAD associated with antecedent or concurrent infection were mostly favorable. Larger prospective epidemiological studies are needed to better delineate the impact of COVID-19 on CNS demyelinating diseases.